Dorsally displaced distal radius fractures: introduction of Pacetti’s line as radiological measurement to predict dorsal fracture displacement - Pace, Valerio; Lanzetti, Riccardo Maria; Venditto, Teresa; Park, Chang; Kim, Woo Jae; Rinonapoli, Giuseppe; Caraffa, Auro (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: In the best of our knowledge there is not yet in the literature a measurement able to assess post reduction stability of distal radius fractures. Aim: to study the relationship between our newly introduced Pacetti’s line, anatomical reduction of DRFs and post-reduction stability of fractures. Methods: Patients/Participants: 230 patients (122men, 108women) who sustained a dorsally displaced distal radius fracture. Close reduction procedures attempted; below elbow cast applied. Follow-up: Pacetti’s line used on true AP and lateral view xrays after reduction and casting (T0) and at 7-14 days (T1-T2). Main Outcome Measurements: Assessment and prediction of early displacement of DRFs. Results: The Pacetti’s line intersected the lunate bone in 162 cases (70.4%) after anatomical reduction, of which 20.4% (N=33) lost anatomical reduction. Cramer’s V test: signiﬁcant relationship between transition of Pacetti’s line through the semilunar bone and stability of anatomical reduction at T0 follow-up (p<0.001, Cramer’s value=0.83). The Pacetti’s line intersected the lunate bone in 119 cases (51.7%) at 7-14 days follow-up. None of patients lost anatomical reduction. Cramer’s V test: signiﬁcant relationship between transition of Pacetti’s line through the semilunar bone and stability anatomical reduction at T1 and T2 follow-up (p<0.001, Cramer’s value=0.73). Conclusions: We strongly recommend the use of the Pacetti’s line as it seems to provide reliable prediction of further fracture displacement and consequently of definitive management. The Pacetti’s line seems to represent a very useful tool providing simple, feasible, efficient and reliable information on DRFs characteristics and natural course.